High Prevalence of Candida Yeast in Milk Samples from Cows Suffering from Mastitis in Poland - Bozena Dworecka-Kaszak; Alicja Krutkiewicz; Daniel Szopa; Miroslaw Kleczkowski; Malgorzata Biegańska (The Scientific World Journal)
Mastitis is an economically important disease in which fungi belonging to the genus Candida may participate as etiological agents. This study focused on determining the frequency of fungal isolation and differentiation of fungal species isolated from milk of mastitic cows. Sixty-six milk samples from mastitic cows were studied, and 55 strains of fungi were isolated. Seven different species classified as Candida were identified basing on phenotypic properties, and the dominating species was C. parapsilosis. Genomic DNA was isolated and amplified in PCR with ITS1 and NL2 primers. Amplification products were digested with restriction enzymes HpaII and EcoRI. Amplification of DNA with ITS1 and NL2 primers resulted in products of different sizes. Comparison of product sizes in restriction fragment PCR REA confirmed differences among species. Strains grouped together on the basis of phenotype characteristics differed in restriction fragment profiles. None of the investigated species showed similar genetic profiles.